Metabolic Products of Linalool and Modulation of GABAA Receptors - Milanos, Sinem; Elsharif, Shaimaa A.; Janzen, Dieter; Buettner, Andrea; Villmann, Carmen (Frontiers in Chemistry, 2017)
Terpenoids are major subcomponents in aroma substances which harbor sedative physiological potential. We have demonstrated that various monoterpenoids such as the acyclic linalool enhance GABAergic currents in an allosteric manner in vitro upon overexpression of inhibitory 12 GABAA receptors in various expression systems. However, in plants or humans, i.e. following intake via inhalation or ingestion, linalool undergoes metabolic modifications including oxygenation and acetylation, which may affect the modulatory efficacy of the generated linalool derivatives. Here, we analyzed the modulatory potential of linalool derivatives at 122 GABAA receptors upon transient overexpression. Following receptor expression control, electrophysiological recordings in a whole cell configuration were used to determine the chloride influx upon co-application of GABA EC5-10 together with the modulatory substance. Our results show that only oxygenated linalool metabolites at carbon 8 positively affect GABAergic currents whereas derivatives hydroxylated or carboxylated at carbon 8 were rather ineffective. Acetylated linalool derivatives resulted in non-significant changes of GABAergic currents. We can conclude that metabolism of linalool reduces its positive allosteric potential at GABAA receptors compared to the significant potentiation effects of the parent molecule linalool itself.